Narratives and Ideologies in Instagram Posts by @taulebih.id about LGBT: A Critical Discourse Analysis Using Fairclough's Model - Salma Salsabila (PRASASTI: Journal of Linguistics, 2025)
This study explores the critical discourse analysis (CDA) of narratives on LGBT topics constructed by the Instagram account @taulebih.id, which emphasizes Islamic values in its content. Using Norman Fairclough’s CDA model, the research examines the textual, discursive, and sociocultural dimensions of the account’s posts from December 2022 to August 2024. The findings indicate that @taulebih.id constructs LGBT-related narratives as moral threats, framing the issue through religious and traditional lenses. The textual analysis highlights the use of persuasive and directive language to reinforce Islamic teachings, while the discursive analysis reveals strategies to engage Muslim audiences with simplified and relatable content. Socioculturally, the account reflects a tension between modern global values and local religious norms, positioning family and education as safeguards against perceived external influences like LGBT movements. This study contributes to understanding how digital religious platforms shape public perceptions of sensitive social issues, emphasizing the role of ideology in discourse construction.